The effect of rotor aspect ratio, stages, and twist angle on Savonius wind turbine performance in low wind speeds environment - Ivan Farozan; Tubagus Ahmad Fauzi Soelaiman; Priyono Soetikno; Yuli Setyo Indartono (Results in Engineering)
The Savonius wind turbine is considered suitable for use in a low wind speed site due to its omnidirectional and good self-starting ability. Therefore, this study aimed to evaluate the Savonius wind turbine performance with various aspect ratios, number of stages, and twist angles when placed in a low wind speed environment. Wind tunnel experiments were performed to obtain the turbine's static torque coefficient, self-starting wind speed, and power coefficient. A continuous observation of wind speed and the direction of an urban site was performed and analyzed using the Weibull distribution function. The experimental and the site wind assessment data were correlated to evaluate the average power output of each turbine. The result showed that the self-starting wind speed for a conventional Savonius rotor fluctuated due to variations in the rotor's azimuth angle. It was discovered that increasing the number of stages and twist angle, or lowering the aspect ratio, caused a reduction in the starting wind speed magnitudes and fluctuations. Furthermore, the lowest average self-starting wind speed of 2.5 m/s was achieved by a turbine with a 90° twist angle, while the highest power coefficient of 0.201 was produced at 45°. Despite the lower power coefficient of 0.184 compared to a conventional Savonius wind turbine at 0.190, the turbine with a 90° twist angle produced a significantly higher average power output ranging from 1.6 to 5.1 times. This finding showed the importance of starting wind speed for the Savonius wind turbine in a low wind speed environment.